Generation and Transmission of Environmental Knowledge and Land Skills in Adaptation to Climate Change in Ulukhaktok, NWT - Pearce, T; Smit, B; Notaina, R; Kudlak, A; Kuneyuna, Z; Wright, Harold (ArcticNet Inc., 2009)
This presentation reports on research that documents and describes how environmental knowledge and land skills are being generated and transmitted among Inuit in Ulukhaktok, Northwest Territories, Canada. In previous research in the Arctic, Inuit have expressed concern that as a result of rapid societal changes, the traditional modes of intergenerational knowledge transmission by which Inuit have developed the skills to hunt safely and successfully no longer function effectively. Younger generation Inuit are spending considerably less time involved in subsistence activities beyond organized land-camps and occasional hunting trips but comparatively more time engaged in formal education and wage employment. This has implications for culture, health and well-being, and for adaptation to changing climatic conditions. The transmission of 92 items of Inuit environmental knowledge and land skills was studied with a sample of 42 Inuit males between the ages 18 and 49 years in Ulukhaktok (approximately 50% of the potential sample). Data were collected through semi-structured interviews, free-listing and pile sorts. The general objectives of the interviews were to learn if an informant had learned a particular skill, if yes, who was their major teacher, how did they learn this skill, how old were they when they learned the skill, and what factors helped facilitate or impede transmission. The results are expected to inform initiatives to help facilitate the transmission of land skills and related environmental knowledge, many already underway, in the Inuvialuit Settlement Region and elsewhere in the Arctic.